Threatened Mangroves in the Anthropocene: Habitat Fragmentation in Urban Coastalscapes of Pelliciera spp. (Tetrameristaceae) in Northern South America - Blanco-Libreros, Juan F.; Ramírez-Ruiz, Karla (Frontiers in Marine Science, 2021)
Mangroves are fragmented habitats thriving in human-dominated coastalscapes worldwide. They provide refuge to threatened plant species, such as the Neotropical Piñuelo Mangrove (formerly the monotypic Pelliciera genus, recently split into two species: P. rhizophorae and P. benthamii). However, little is known about the relationship between urbanization and the spatial configuration of mangrove habitat and how it would drive ecological and evolutionary changes in the small populations of Pelliciera spp. We used open data (e.g., land cover, mangrove cover) for 107 locations of Pelliciera spp. in Colombia (extant populations) to assess coastalscape structure and urbanization. We described coastalscape composition dynamics (for 2000 and 2010) and mangrove habitat configuration along a human-domination gradient, using landscape metrics. We computed an urban index to compare urbanization intensity among the study areas along the Caribbean coast and compared coastalscape structure and mangrove spatial metrics between basins (Caribbean and Pacific). The proportion of artificial surfaces was greater in the Caribbean than in the Pacific, but no temporal difference was found. The Caribbean basin exhibited a greater Urban Index, particularly in Cartagena and Urabá. Mangrove fragmentation was also greater in the Caribbean and it was influenced by the degree of urbanization. Mangrove area and core area were smaller in the Caribbean than in the Pacific, while cohesion was significantly lower in Cartagena than in other urban areas of the Caribbean. We propose a conceptual eco-evolutionary framework for linking mangrove patch reduction and isolation to demographic variables of Pelliciera spp. Edge effects are expected to affect birth and mortality rates in small patches. Small patches and small effective populations are expected to be more sensitive to novel biotic interactions, extreme weather, and gradual climate change. Isolation will also influence both emigration and immigration rates of propagules. We propose: (1) Assessing the conservation status of the two species, (2) setting monitoring programs of their populations of Pelliciera spp. and their surrounding coastalscapes (particularly in the Caribbean, (3) declaring protected areas, in wild and urban settings, to reduce mangrove fragmentation and urbanization.